Liberibacter, A Preemptive Bacterium: Apoptotic Response Repression in the Host Gut at the Early Infection to Facilitate Its Acquisition and Transmission - Tang, Xiao-Tian; Fortuna, Kelsy; Mendoza Herrera, Azucena; Tamborindeguy, Cecilia (Frontiers in Microbiology, 2020)
‘Candidatus Liberibacter solanacearum’ (Lso) is a phloem-limited Gram-negative bacterium that infects crops worldwide. In North America, two haplotypes of Lso (LsoA and LsoB) are transmitted by the potato psyllid, Bactericera cockerelli (Sulč), in a circulative and persistent manner. Both haplotypes cause damaging plant diseases (e.g., zebra chip in potatoes). The psyllid gut is the first organ Lso encounters and could be a barrier for its transmission. However, little is known about the psyllid gut immune responses triggered upon Lso infection. In this study, we focused on the apoptotic response in the gut of adult potato psyllids at the early stage of Lso infection. We found that there was no evidence of apoptosis induced in the gut of the adult potato psyllids upon infection with either Lso haplotype based on microscopic observations. However, the expression of the inhibitor of apoptosis IAPP5.2 gene (survivin-like) was significantly up-regulated during the period that Lso translocated into the gut cells. Interestingly, silencing of IAPP5.2 gene significantly up-regulated the expression of two effector caspases and induced apoptosis in the psyllid gut cells. Moreover, RNAi of IAPP5.2 significantly decreased the Lso titer in the gut of adult psyllids and reduced their transmission efficiency. Taken together, these observations suggest that Lso might repress the apoptotic response in the psyllid guts by inducing the anti-apoptotic gene IAPP5.2 at an early stage of the infection, which may favor Lso acquisition in the gut cells and facilitate its transmission by potato psyllid.